Human longevity : omega-3 fatty acids, bioenergetics, molecular biology, and evolution - Valentine, R. C. 1936-; Valentine, David L. (Taylor & Francis, 2015)
"Human cells are protected from the ravages of aging by defensive systems including novel mechanisms against membrane oxidation introduced in this book. The book proposes a unified concept in which aging cells faced with declining energy production by mitochondria and the relatively high cost of protecting membranes against oxidation are triggered by energy stress to activate programmed cellular death. It includes case histories illustrating the duality of polyunsaturated membranes in aging and longevity. It also explains the relationship between membrane unsaturation and longevity leading to a unified concept of aging. "-- Provided by publisher.
Keywords: Aging -- Genetic aspects.; Mitochondria.; Oxidative stress.; Omega-3 fatty acids -- Health aspects.; elektronické knihy; electronic books